2015
DOI: 10.1111/ppe.12263
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette‐Guérin (BCG) Vaccination in Infancy and Risk of Childhood Diabetes

Abstract: Background: A narrow time window in infancy may be relevant for the aetiology of immune-mediated type 1 diabetes. We investigated whether a non-specific immune stimulation in the first year of life, as resulting from Bacillus Calmette-Guérin (BCG) vaccination, was associated with childhood diabetes. Methods: Using data from a birth cohort assembled through linkage of administrative databases, 78 492 subjects born in 1974 were the object of the present analysis. Information was extracted from the birth, death, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Lastly, as BCG is able to induce trained immunity, it could be expected that BCG-vaccinated children are at higher risk to develop T1DM. However, in an observational trial no such correlation has been found ( 214 , 215 ). Interestingly, in a randomized controlled trial, BCG was suggested to have a beneficial effect on insulin production, as induction of TNF production resulted in reduced autoimmune phenotype of innate immune cells and induction of Tregs ( 216 , 217 ).…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 87%
“…Lastly, as BCG is able to induce trained immunity, it could be expected that BCG-vaccinated children are at higher risk to develop T1DM. However, in an observational trial no such correlation has been found ( 214 , 215 ). Interestingly, in a randomized controlled trial, BCG was suggested to have a beneficial effect on insulin production, as induction of TNF production resulted in reduced autoimmune phenotype of innate immune cells and induction of Tregs ( 216 , 217 ).…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 87%
“…Clinical data have shown no association between BCG vaccination and type 1 diabetes or islet autoimmunity. A 20 year follow-up of the 1974 Canadian birth cohort, of which 45% were given BCG in the first year of life, showed no association with type 1 diabetes, 54 nor did case-control studies from Canada 55 and Sweden. 56 The German BABYDIAB study 57 reported no association between BCG vaccination and development of islet autoimmunity.…”
Section: Vaccinesmentioning
confidence: 92%
“…However, in some paediatric studies, where time‐varying exposures are measured, conventional survival model based on time‐fixed analysis is still widely adopted. Some example studies include identifying factors associated with breast‐feeding duration, assessing the relationship between vaccination and childhood diabetes, and determining neonatal factors affecting the development of childhood epilepsy . Time‐varying exposures are often treated as time‐fixed variables over the entire follow‐up period, which may lead to incorrect inferences …”
Section: Introductionmentioning
confidence: 99%